Scapha Wristband / Liz Irdina Rozaini, Aina Hayati Mohd Ramli and Nur Hannani Dzulkifli - Rozaini, Liz irdina; Mohd Ramli, Aina Hayati; Dzulkifli, Nur Hannani (2022)
This concept will be developed in the twenty-first century. This endeavour will be a first in the airline business. Because some airlines will disregard or overlook the services they could provide. This development is particularly significant for the airline sector because it has the potential to help the company grow and become more profitable. Because innovation and project go hand in hand when they are developed, they can be run as a project. We shall apply the concept of innovation project management and specify the traditional project in this project. We can contribute to the academic programme and the debate between innovation and project management by implementing this innovation.